PENATALAKSANAAN TERAPI RADIASI PADA KEGANASAN RONGGA MULUT - Raden Susworo; Ratna Meidyawati; Harum Sasanti (Journal of Dentistry Indonesia, 2015)
Radiotherapy as a treatment of modality, aside from other modalities such as surgery and chemotherapy, has been achieved not far off the discovery of X ray at the end of 19th century. Combined external radiation and brachytherapy on the treatment of oral cavity malignancies has shown good result with reasonable toxicities. Mechanism of radiotherapy, radiophysics and radiobiology will be discussed briefly on this paper. The indications of radiotherapy and toxic effects may arise will also be discussed .